Plant cover and land degradation relationship on Aegean coastal zone - Nurlu E.; Erdem U.; Guvensen A.; Yilmaz O. (Environmental monitoring in the South-Eastern Mediterranean region using RS/GIS techniques, 2003)
Two different areas of the Karaburun peninsula (Turkey) were selected on the basis of variability of natural characteristics, demographic developments, settlements and land use on the peninsula. Supervised and unsupervised classifications were used to obtain land cover data. LANDSAT 7 image recorded in September 2000, together with ancillary data were used to create land cover maps for the study area. ERDAS Imagine 8.4 and Arc View 8 were used to interpret the image and to integrate it into geographical information system. The methodology consists of computer-assisted photo interpretation of satellite data by using ancillary data and field observations. The land cover classes on the created maps were obtained according to the CORINE standards (CORINE Land Cover Nomenclature). Plant communities, showing dominant distribution characteristics and other accompanying taxa were identified in areas where GPS points were taken. More than 50 percent of the area is covered with forests and semi-natural areas. 30.9 percent of the natural protection sites lie in the Western part and 7.9 percent in the East. The main factor for land degradation appear to be the second house constructions. There is an urgent need for enlargement of natural protection sites using the obtained land/plant cover data.